A study of parental decision-making over the vaccination of girls, based on the protection motivation theory and the elaboration likelihood model - Wang, Qi; Zhou, Fangzhou; Zhang, Wen; Tang, Chenjin (Frontiers in Public Health, 2022)
This study proposed a new theoretical framework that combines the protection motivation theory and the elaboration likelihood model to examine how health information processing patterns influence parents' vaccination decision-making on behalf of their daughters. Based on survey data from 359 parents of girls aged 9–15, we tested the theoretical model by using structural equation model. The results showed that the central route, represented by information quality, affected the parents' perceptions of HPV severity and susceptibility; the peripheral route, represented by source credibility, influenced their perceptions of HPV severity, HPV susceptibility, vaccine response efficacy, and secondary risks. Also, Chinese parents' perceptions of HPV vaccines, not perceptions of HPV, affected their intention to vaccinate their daughters. The study suggests in addition to improving the quality of health information, the peripheral route, such as the release of vaccination photos, public immunization evaluations, and case narratives, should also be used to change parents' perceptions. Besides, reducing the traditional stigmatization of female sexuality and improving parents' understanding of the new generation's sexual attitudes will increase parents' intention to have their daughters vaccinated against HPV.